1985
DOI: 10.1039/c39850000456
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular interactions in bis(pentamethylcyclopentadienyl) complexes: X-ray structures of (η5-C5Me5)2Zr(OH)(Cl) and (η5-C5Me5)2Zr(OH)2

Abstract: The structures of (q5-C5Me5),Zr(0H)(CI) (1) and ( T ~-C ~M ~~) ~Z ~( O H ) ~(2) have been determined by X-ray diffraction; location of all hydrogen atoms in (1) has established the presence of significant intramolecular non-bonding contacts and (2) is the first early transition metal dihydroxo complex to be structurally characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 1 publication
5
22
0
Order By: Relevance
“…2 Compound 3 represents a bent metallocene sandwich. The value of Cp(cent)-Zr-Cp(cent) angle (135.8°) compares well with those found for (C 5 Me 5 ) 2 Zr(OH)Cl -137.9° [5] and (C 5 Me 5 )(C 5 Me 4 CH 2 CH 2 NMe 2 )ZrCl 2 -136.9° [1]. Both cyclopentadienyl rings are planar within 0.023(3) Å .…”
Section: X-ray Structural Studies Of Complexes 2 Andsupporting
confidence: 81%
See 1 more Smart Citation
“…2 Compound 3 represents a bent metallocene sandwich. The value of Cp(cent)-Zr-Cp(cent) angle (135.8°) compares well with those found for (C 5 Me 5 ) 2 Zr(OH)Cl -137.9° [5] and (C 5 Me 5 )(C 5 Me 4 CH 2 CH 2 NMe 2 )ZrCl 2 -136.9° [1]. Both cyclopentadienyl rings are planar within 0.023(3) Å .…”
Section: X-ray Structural Studies Of Complexes 2 Andsupporting
confidence: 81%
“…The measurements of the NOE enhancement values, with protons Zr-H, CH 3 (5), CH 3 (4), NCH 3 , H(8a) and H(8b) consecutively irradiated, made it possible to perform the complete assignment of the signals in the NMR spectra and to determine the conformation of the Zr-C(1)-C(6)-C(7)-N-C(8)-(Zr) framework metallacycle as a one resembling a pseudo-six-member boat. These NMR spectroscopy data for complex 2 in a solution are in an excellent agreement with the X-ray diffraction analysis data (vide infra).…”
Section: Reduction Of Zirconocene Dichloride 1 With Amalgamated Magnementioning
confidence: 99%
“…The loss of the polymeric structure found in Zr(¢-CsHs)CI3 must be attributed to the formation of the hydroxo adduct, trans to the cyclopentadienyl group. The Zr(1 )--O (1) bond distance of 2.321(4) A is comparable to that found in other monocyclopentadienyl zirconium adduct complexes such as Zr(t/5-CsHs)CI3 • 2THF (2.393 and 2.314 A) or Zr(r/s-CsH4Me)C13 • 2THF (2.377 and 2.310 A) [24], although higher than that observed for terminal hydroxo complexes such as Zr(~IS-CsMes)2(OH)2 (1.982 and 1.975 A) [25] or Zr(r/s-CsM%)2(OH)CI (1.950 A) [25].…”
Section: Description Of the Crystal Structure Of [Zr{qs-csh4mentioning
confidence: 55%
“…3(8) 3 }] (4), a rare example of a terminal hydroxo complex of a zirconocene. Stabilisation by the sterically bulky Cp* ligands prevents dimerisation with formation of oxo bridges, which usually occurs with elimination of water, [15] as first described by Hillhouse et al [16] and Bortolin et al [17] Complex 4 is the first heteroleptic carboxylato hydroxo complex structurally characterised by X-ray crystallography. Pellny et al reported the NMR spectroscopic observation of the compounds [Cp* 2 Zr(OH){OOC-C(SiMe 3 )=CHPh}] and [Cp* 2 Zr(OH){OOC-CPh=CH(SiMe 3 )}], but could not isolate them.…”
Section: Mono(carboxylato)zirconocene Complexesmentioning
confidence: 96%
“…[17,19] The O3···O1 distance of 272.1 pm seems to indicate the presence of a hydrogen bond between them. As the C46···O1 distance in 3 is also only 274.6 pm, it appears that the two atoms are forced into close proximity due to the high steric demand of the Cp* rings.…”
Section: Mono(carboxylato)zirconocene Complexesmentioning
confidence: 99%